Empirical Determinants of Household Saving : Evidence From OECD Countries - Callen, Tim (IMF Working Papers; Working Paper ;, 1997)
This paper analyzes the empirical determinants of household saving using data from 21 OECD countries for 1975-95. A particular focus is the influence of the tax and social security systems on household saving. The paper therefore extends the usual set of explanatory variables used to explain household saving behavior to include variables that capture the structure of the tax system and the financing and generosity of the social security and welfare system. These variables are found to have an important impact on household saving. Accordingly, by changing the design of these systems, governments may be able to influence saving.